Boosting regional socioeconomic development through logistics activities: A conceptual model - Tiago Vieira; Ângela Silva; Jorge Esparteiro Garcia; Wellington Alves (Business Systems Research (BSR), 2022)
Background: Regional Development (RD) allows countries to balance regional differences by providing economic and social benefits to communities. This research highlights the importance of logistics activities to regional social development, and a framework to assess these connections is proposed. Objectives: How to boost regional socioeconomic development through logistics. Methods/Approach: The contributions of logistics to socioeconomic development are analysed based on the previous research, and the case of the Alto Minho (AM) region in Portugal was used to illustrate the connection between logistics and regional development. Results showed that logistics had created jobs, increased company turnover and exports, and increased GDP growth in several regions. For the AM region, results indicate that many companies are operating in this area, contributing to supporting municipalities to reduce regional disparities. Conclusions: A framework for assessing regional logistics performance is proposed together with several logistics performance indicators. This approach is essential for future developments integrating logistics into socioeconomic development.
Keywords: L16; 330; Logistics; Regional development; Logistics Performance Index; Portugal